Implementation of Android-Based Flutter Framework and Waterfall Method in Building Marketplace Applications (MariUmroh) - Mardiah Ramadhani; Ilka Zufria; Ali Ikhwan (Research Group of Data Engineering, Faculty of Informatics, 2024)
The MariUmroh application is an Android-based Umrah and Hajj travel marketplace application designed specifically to bring together sellers and buyers in one digital platform. The MariUmroh marketplace application aims to make it easier for prospective pilgrims and Umrah and Hajj travel companies to interact, transact, and promote their products online. In its business processes, the MariUmroh application uses a B2C (Business to Customer) business model. Where business activities are carried out by travel admins to customers using electronic media directly. The development of the Android-based MariUmroh application is built with the Flutter Framework which uses the Dart programming language. In building the MariUmroh marketplace application, the development system uses the waterfall method, in its creation it begins with needs analysis, system design, program code writing, program testing, program implementation and maintenance. In the MariUmroh application which offers various Umrah and Hajj travel packages to the wider community easily and more efficiently, and sellers easily promote their products and don't have to worry about losing consumers, the features provided by the application are also very useful for pilgrims during their worship at holy land. In building this application, MySQL is used as a database for data storage. Keywords: Marketplace, Umrah and Hajj travel, flutter framework, Waterlfall